IDENTIFICATION OF TREE VEGETATION IN PASIR PUTIH COASTAL FOREST TOURISM AREA, ACEH BESAR REGENCY - Warah, Muna; Hidayat, Muslich (Center for Environmental Studies, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Tree vegetation plays a crucial role in maintaining ecosystem balance, particularly in preventing erosion and sediment loss in Pasir Putih Beach Tourism Area. This study aims to identify and analyze the density of tree vegetation in Pasir Putih coastal forest located in Aceh Besar Regency. Tree vegetation plays a crucial role in maintaining ecosystem balance, particularly in preventing erosion and sediment loss in Pasir Putih Beach Tourism Area. This study aims to identify and analyze the density of tree vegetation in Pasir Putih coastal forest located in Aceh Besar Regency. The research employed the Point Centered Quarter (PCQ) method, dividing the study site into three observation stations. At each station, a 100meter transect line was established with four sampling points per station, where the nearest tree to each point was measured and recorded. The environmental parameters observed included temperature, soil pH, soil moisture, and air humidity. The findings revealed a total of 11 tree species belonging to 11 families, consisting of 41 individual trees across all stations. The most dominant species in Pasir Putih Beach Tourism Area was Avicennia marina (grey mangrove), with 20 individual trees. Based on data analysis, the tree density at transect one was 0.0420, at transect two was 0.0371, at transect three was 0.0625, and the overall tree density across all transects was 0.0455.